2022
DOI: 10.1111/plb.13448
|View full text |Cite
|
Sign up to set email alerts
|

Do water and soil nutrient scarcities differentially impact the performance of diploid and tetraploid Solidago gigantea (Giant Goldenrod, Asteraceae)?

Abstract: Plants require water and nutrients for survival, although the effects of their availabilities on plant fitness differ amongst species. Genome size variation, within and across species, is suspected to influence plant water and nutrient requirements, but little is known about how variations in these resources concurrently affect plant fitness based on genome size. We examined how genome size variation between autopolyploid cytotypes influences plant morphological and physiological traits, and whether cytotypesp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 108 publications
(285 reference statements)
2
11
0
Order By: Relevance
“…Unlike the reported in some studies (e.g., Pavlıḱováet al, 2017;Martıńez et al, 2018), the neotetraploids and established tetraploids did not perform better under water deficit conditions than diploids as indicated by negative responses in total biomass production and lack of differences in the F v /F m and F PSII . Similar results were found by (Walczyk and Hersch-Green, 2022) for diploid and tetraploid Solidago gigantea, in which cytotypes did not differ in biomass and photosynthetic efficiency in response to water deficit. Regardless of whether the ecological differences arose in association with or after genome duplications, niche differentiation has been suggested as a key factor for the successful establishment of polyploids.…”
Section: Do Var Maritima Diploids Neotetraploids and Established Tetr...supporting
confidence: 84%
See 2 more Smart Citations
“…Unlike the reported in some studies (e.g., Pavlıḱováet al, 2017;Martıńez et al, 2018), the neotetraploids and established tetraploids did not perform better under water deficit conditions than diploids as indicated by negative responses in total biomass production and lack of differences in the F v /F m and F PSII . Similar results were found by (Walczyk and Hersch-Green, 2022) for diploid and tetraploid Solidago gigantea, in which cytotypes did not differ in biomass and photosynthetic efficiency in response to water deficit. Regardless of whether the ecological differences arose in association with or after genome duplications, niche differentiation has been suggested as a key factor for the successful establishment of polyploids.…”
Section: Do Var Maritima Diploids Neotetraploids and Established Tetr...supporting
confidence: 84%
“…Tetraploids tend to have higher contents of chlorophyll and carotenoids (e.g., Cao et al, 2018;Mao et al, 2018) and sugars (Mao et al, 2018) when compared to diploids, which may confer higher protection against excess light energy. Tetraploids also tend to have larger but fewer stomata resulting in lower transpiration rates, as shown for several plant species [e.g., Jasione maritima (Siopa et al, 2020), Arabidopsis (Del Pozo and Ramirez-Parra, 2014), Solidago gigantea (Walczyk and Hersch-Green, 2022)]. Additionally, tetraploids tend to be bigger and have higher fitness than diploids, which may facilitate their establishment (Ramsey, 2011;del Pozo and Ramirez-Parra, 2015) and can have larger leaf thickness (van Laere et al, 2011) or epidermis thickness and pubescence (Li et al, 1996, Li et al, 2009, which may result in higher tolerance to stressful factors.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Belowground interaction among plants may affect aboveground biomass in nutrient-competitive environments. Limited nutrient availability influences plant biomass production [ 33 , 34 ]. Overall, we found that total dry mass and shoot dry mass were greater for the kin connected plants than non-kin connected plants ( Table 1 , Figure 1 ), and the differences were greater under high nutrients relative to low nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we predicted that because photosynthesis and terpenes (a defensive compound within Solidago; Bohlmann et al, 1998;Bustamante et al, 2020;Ninkuu et al, 2021) both directly or indirectly (from precursor production) require N and P, that photosynthetic rates and terpene concentrations would be (1) higher under nutrient enrichments, (2) lower for larger GS cytotypes (due to material cost and photosynthesis/defense trade-offs), and (3) more similar among cytotypes under nutrient enrichments because larger GS cytotypes should be less constrained by material costs. (H5) Because stomatal density is negatively correlated with ploidy level in S. gigantea (Walczyk and Hersch-Green, 2022;Walczyk, 2022), larger GS cytotypes have lower transpiration rates and combined with how GS and nutrient availability influences photosynthesis (see H4) will also be more water-use efficient (able to assimilate more carbon from photosynthesis than water lost from transpiration) than smaller GS cytotypes, especially under nutrient-limiting conditions. (H6) Larger GS cytotypes are more nutrient-use efficient under nutrient limiting conditions, thereby minimizing increased material-cost constraints.…”
mentioning
confidence: 99%